Unlocking Career Potential: How Micro-Credentials Are Revolutionising Higher Education and Lifelong Learning - Kelum A. A. Gamage; Shyama C. P. Dehideniya (Education Sciences)
Micro-credentials (MCs) emerged as a powerful tool to advance employability and lifelong learning while opening opportunities for diverse career directions for individuals. They are generally short programmes and have a specific focus on developing complementary skills in a particular area of interest for the learner. This paper presents a critical narrative review exploring the transformative potential of micro-credentials, which provide targeted, flexible, and accessible pathways for skill development and career advancement. It examines how micro-credentials bridge the gap between traditional education and modern industry demands and recognises the importance of collaborative efforts between higher education and industry in identifying and sometimes even co-designing relevant micro-credential programmes. Additionally, the paper analyses the impact of micro-credential programmes on non-traditional learners and discusses the mechanisms to ensure the quality and credibility of such programmes. The findings highlight four key thematic areas, revealing that micro-credentials serve as flexible, inclusive tools that enhance employability, support institutional innovation, and promote lifelong learning.